MULTIPLE DRONES PATH OPTIMIZATION ALGORITHM FOR 3D SPACE PERFORMANCE USING CENTRALIZED VISUALIZATION PLATFORM - Teng, Chu Yao (Universiti Malaysia Sarawak (UNIMAS), 2019)
Path planning algorithm of Unmanned Aerial Vehicle (UAV) subject to find an optimal and collision free path in 3D space. With the popularization of UAV application, the drones are now can perform visualization by orderly flying within the airspace. However, UAVs face problem that low battery life when performing flying mission. Many algorithms have been done by researchers to solve the fast energy consumption problem. The existing methods aim for planning optimal path of drone flight. In this report, a variant of A*, Theta* algorithm is proposed to find the optimal path within a grid-based environment. The reason of choosing this algorithm is that Theta* is fast and simple that able to find the shortest and realistic path. The proposed algorithm, with the inclusion of the triangle theorem, is utilized in this project to further boost performance of drones in trajectory planning. The result of this project conclude that proposed algorithm able to optimized the A* algorithm in term of total path travelled, maximum path travelled by single drone and number of turn. After testing with designed stimulator, results also prove that the efficiency of the proposed algorithm is higher under certain space occupancy.